2010
DOI: 10.1158/0008-5472.can-09-4656
|View full text |Cite
|
Sign up to set email alerts
|

HuR Regulates β-Tubulin Isotype Expression in Ovarian Cancer

Abstract: The supply of oxygen and nutrients to solid tumors is inefficient because cancer tissues have an inadequate number of microvessels, thus inducing the selective growth of the most aggressive cancer cells. This explains why many of the factors underlying a poor prognosis are induced in hypoxic/hypoglycemic conditions. Among these factors, a prominent role in several solid tumors is played by the class III β-tubulin gene (TUBB3). The study described here reveals that glucose deprivation enhances TUBB3 expression … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 24 publications
(28 reference statements)
6
75
0
Order By: Relevance
“…In females the expression of both TUBB3 HuR and TUBB6 was higher in patients with metastatic disease. Therefore in females, the same pathway that we previously reported in ovarian cancer (6,15,19) is implicated. On the other hand, if these 2 biomarkers are not expressed, the disease seems less aggressive and the outcome better.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In females the expression of both TUBB3 HuR and TUBB6 was higher in patients with metastatic disease. Therefore in females, the same pathway that we previously reported in ovarian cancer (6,15,19) is implicated. On the other hand, if these 2 biomarkers are not expressed, the disease seems less aggressive and the outcome better.…”
Section: Discussionsupporting
confidence: 76%
“…To our knowledge this is the first article addressing the role of TUBB3 in colorectal cancer. Recent findings support the notion that the TUBB3 pathway is an adaptive response to exposure to microenvironmental stressors, such as hypoxia and poor nutrient supply (5,6). For this reason TUBB3 is a biomarker of biologic aggressiveness and the tendency toward metastasis (7).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…These findings together support the potential clinical utility in the refractory NACT setting (exhibiting high HGF (protein/gene) and low MET gene high c-Met protein) of the inhibition of both c-Met and HGF. It has been demonstrated that a block of translation can produce an apparent upregulation of the most transcribed genes, thus demonstrating a feedback loop between translation and mRNA degradation [24][25][26]. On the opposite, enhancement of translation can be accompanied by decrease of mRNA stability and consequent reduced mRNA levels [24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in addition to GEM, high HuR expression levels may regulate the response to paclitaxel via regulation of chemoresistance-associated factors including microRNA (31,32). A previous in vitro study demonstrated that cytoplasmic HuR expression was associated with the efficacy of various anticancer agents (33-35); however, it has also been revealed that HuR is able to mediate chemoresistance in numerous types of cancer (36,37). Further studies are required in order to investigate and elucidate the complex mechanisms underlying the interaction between HuR expression levels and the response of patients to chemotherapy.…”
Section: Univariate Analysismentioning
confidence: 99%